Conor McPherson's The Seafarer: tinkering with tradition - Roberto Ferreira da Rocha (Ilha do Desterro, 2010)
A reading of The Seafarer (2007), the last published play by the Irish playwright Conor McPherson (1971- ), which aims to investigate the rich intertextuality that the work presents. The text echoes both canonic and popular renderings of the Faustian myth, those of Christopher Marlowe (c. 1564-1593) and Johann Wolfgang Goethe (1749-1832), as well as its folk rewritings. In The Seafarer McPherson conveys a complex portrait of a group of Irish working-class mates, who are enthralled in existential and gender conflicts. In this his fourth full-length ensemble play to reach both the London West End and New York Broadway (the first being The Weir of 1999) McPherson critically dialogues with the modernist and postmodernist dramatic tradition mainly through the works of John Middleton Synge (1871-1909), Samuel Beckett (1906-1989), Harold Pinter (1930-2008) and David Mamet (1947- ), without losing, however, a genuine sense of deep Irishness.